Seroprevalence of Borrelia burgdorferi in Stray Dogs from Southern Italy - Galluzzo, Paola (Microorganisms, 2020)
Borrelia burgdorferi is a bacterial pathogen transmitted by Ixodes ticks and is responsible for Lyme disease in both humans and dogs. The aim of this work was to evaluate B. burgdorferi diffusion among stray dogs in Palermo (Sicily, Italy) by serological methods in order to study the risk factors associated with the infection. Serum and blood samples of 316 dogs were collected from a shelter in Palermo, and were analyzed for the presence of antibodies against B. burgdorferi by indirect immunofluorescence assay (IFA), and of the ospA gene by real-time PCR, respectively. Seventeen sera (5.4%) were positive for the antibodies via IFA and one blood (0.3%) for ospA via real time PCR. On the basis of serological results, the evaluation of the potential risk factors (sex, age, breed and coat color) was carried out. The multivariate analysis indicated that male sex is a factor significantly associated with B. burgdorferi seropositivity. This study confirms that male dogs have a higher risk of developing the disease than females, and represents the first investigation on the spread of B. burgdorferi among stray dogs in Sicily.